1967
DOI: 10.3133/pp566
|View full text |Cite
|
Sign up to set email alerts
|

Younger Precambrian geology in southern Arizona

Abstract: ________________ Thickness and distribution of younger Precambrian rocks. Apache Group____________________________________ Pioneer Shale__________________________________ Thickness and general character-_____________ Lithology and stratigraphic relations-_________ Scanlan Conglomerate Member...________ Tuffaceous mudstone..__________________ Arkose._______________________________ Lateral variations.._________________________ Dripping Spring Quartzite___-_-___-_________ Barnes Conglomerate Member_______________… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 18 publications
(15 reference statements)
2
17
0
Order By: Relevance
“…Shride (1967) measured potassium oxide concentrations greater than 10 percent in the argillite member of the Me seal, and Shride (1967) and Granger and Raup (1969b) observed that asbestos mineralization in the Me seal commonly has magnetite associated with it.…”
Section: Geologymentioning
confidence: 99%
See 1 more Smart Citation
“…Shride (1967) measured potassium oxide concentrations greater than 10 percent in the argillite member of the Me seal, and Shride (1967) and Granger and Raup (1969b) observed that asbestos mineralization in the Me seal commonly has magnetite associated with it.…”
Section: Geologymentioning
confidence: 99%
“…The magnetic data were obtained because iron deposits are known in the area and because iron mineralization occurs in association with known asbestos deposits (Shride, 1967(Shride, , 1969* The radiometric and magnetic data are presented as contour maps overlaid on geologic and topographic maps* METHOD An aerial radiometric survey measures gamma radiation from the decay products of the radioelements K-40, U-238, and Th-232. The distribution of these elements and their decay products are controlled by the complex interaction of geological and geochemlcal processes such as hydrothermal fluid movement, groundwater flow, weathering, erosion, and transportation* Because of this relationship to geologic processes, measurements of the radioelement distributions can be used to aid geologic mapping and mineral exploration* The measurement of the radioelement distributions is made using scintillation detectors with associated electronic equipment* The survey aircraft generally follows the contour of the ground with a ground clearance of no more than 220 m (700 ft)* The low ground clearance Is -necessary for statistically valid measurements because the gamma rays are absorbed at an exponentially increasing rate as the thickness of the air beneath the aircraft increases* Because the gamma-ray absorption by the surface materials also increases ' exponentially, the measurements reflect the radioelement concentrations only in the uppermost 0*5 m (1*5 ft) of rock and soil at the ground surface.…”
mentioning
confidence: 99%
“…The Apache Group is present only in the Rincon and Little Dragoon Mountains; the rocks are more widespread and more completely preserved north of the region (Shride, 1967) and are probably eroded from the rest of the southeastern Arizona region. Both the basal Scanlan Conglomerate Mem her of the Pioneer Shale and the basal Barnes Conglomerate Member of the Dripping Spring Formation are present.…”
Section: Precambrian Rocksmentioning
confidence: 99%
“…ag~, the sea transgressed the region and a second suite of Precambrian rocks, consisting of sedimentary rocks, was deposited, to form the Apache Group (Shride, 1967). Block faulting and intrusion of 1,040-to 1,200-m.y.-old diabase into the Apache Group occurred mainly north of the region.…”
Section: Pre-cordilleran Orogeny Developmentmentioning
confidence: 99%
“…·Named by Ransome ( 1915) -Origin-ally considered Cambrian ·in a.ge, but now known to be Precambrian, as it is intruded by . diabase; overlain paraconformably by Camb.rian and (or) Devonian formations in adjacent areas (Krieger, 1961(Krieger, , 1968a(Krieger, "e, 1973b·_and Shride, 1967 Group, formations, and members named by Ransome (1903), except for' Mescal Limestone (Ransome, 1915) and siltstone and arkose member of Dripping Spring Quartzite (Shride, 1967). …”
Section: Diabasementioning
confidence: 99%